The correlation between educational levels and central obesity in the north of Iran: An epidemiologic study - Veghari, Gholamreza (Isfahan Cardiovascular Research Center, Isfahan University of Medical Sciences, 2013)
BACKGROUND: The main aim of this study was to evaluate the association between educational levels and central obesity in northern Iran in 2010. METHODS: This was a cross-sectional study carried out on 2428 subjects (1227 men and 1201 women) of 15-65 years of age who were chosen by cluster and stratified sampling methods. Subjects were randomly selected from 125 clusters and each cluster included 20 cases. Interviewers recorded the data using a multidimensional questionnaire comprising socio-demographic indexes. RESULTS: Central obesity was seen in 34.8% of all subjects (15.9% male and 56.7% female) and in 15% of uneducated people. In the uneducated group, it was 20.0% and 31.1% higher than in the 1-9 years of schooling and high school or college educated groups, respectively (P = 0.001). The risk of central obesity increased in uneducated people (OR = 4.214, P = 0.001) and in people with 1-9 years of schooling (OR = 2.283, P = 0.001) compared with high school or college educated people. The risk of central obesity was higher in urban areas than in rural area (OR = 1.481, P = 0.001), in women than men (OR = 7.039, P = 0.001), in 40-65 year olds than 15-40 year olds (OR = 3.090, P = 0.001), and in the wealthy economic group than poor economic group (OR = 1.360, P = 0.013). The risk of central obesity increased in urban areas (OR = 2.266, P = 0.001) and the wealthy economic group (OR = 1.732, P = 0.001) after it was adjusted for education. CONCLUSION: Central obesity as a health problem in northern Iran has been supported in this study, and it had an inverse correlation with educational levels. Public health programs that aim to reduce central obesity should mainly focus on the illiterate and low educated people.